2018
DOI: 10.3389/fphys.2018.01448
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Adaptations to High-Load Training and Very Low-Load Training With and Without Blood Flow Restriction

Abstract: An inability to lift loads great enough to disrupt muscular blood flow may impair the ability to fatigue muscles, compromising the hypertrophic response. It is unknown what level of blood flow restriction (BFR) pressure, if any, is necessary to reach failure at very low-loads [i.e., 15% one-repetition maximum (1RM)]. The purpose of this study was to investigate muscular adaptations following resistance training with a very low-load alone (15/0), with moderate BFR (15/40), or with high BFR (15/80), and compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(137 citation statements)
references
References 26 publications
5
132
0
Order By: Relevance
“…Because the patients were women, sedentary (with ~60% sedentary time per day), postmenopausal, fairly functional, and in remission or with mild‐to‐moderate disease activity, these data cannot be extrapolated to patients with different characteristics (e.g., those with a more severe disease). Because we opted for 1RM reassessments throughout the training protocol, one might consider those as supplemental high‐load training sessions, possibly affecting strength gains . However, in the current study, in addition to the control group, the other 2 groups also had multiple familiarization sessions before beginning the trial, and only 2 reassessments were conducted during training (at weeks 4 and 8), which is far less than previously shown to affect strength, thus mitigating a possible confounding effect and strengthening the current design.…”
Section: Discussionmentioning
confidence: 91%
“…Because the patients were women, sedentary (with ~60% sedentary time per day), postmenopausal, fairly functional, and in remission or with mild‐to‐moderate disease activity, these data cannot be extrapolated to patients with different characteristics (e.g., those with a more severe disease). Because we opted for 1RM reassessments throughout the training protocol, one might consider those as supplemental high‐load training sessions, possibly affecting strength gains . However, in the current study, in addition to the control group, the other 2 groups also had multiple familiarization sessions before beginning the trial, and only 2 reassessments were conducted during training (at weeks 4 and 8), which is far less than previously shown to affect strength, thus mitigating a possible confounding effect and strengthening the current design.…”
Section: Discussionmentioning
confidence: 91%
“…To illustrate, studies implementing body weight exercise have found increases in muscle size but not necessarily changes in voluntary strength [16,17]. This is corroborated by two additional studies with very low load resistance exercise where muscle growth appeared to change but strength in the task they were training did not [18,19]. When considered together, there is strong evidence that muscle growth is not necessary for an increase in strength and some evidence that muscle growth is also not sufficient for an increase in strength.…”
Section: Sufficient?mentioning
confidence: 92%
“…24 Insight into the generality of strength adaptation can also be gained from the low load training literature. Jessee et al 25 noted a 10% increase in isotonic knee extensor 1RM strength following isotonic training at moderate training load (70% 1RM). The study also included three very-low load training conditions (15% 1RM with and without blood flow restriction) that observed no meaningful changes in isotonic knee extensor strength.…”
Section: The Generality Of Strength Adaptationmentioning
confidence: 99%